Entrepot for Chinese Consumer Goods in Central Asia : The Puzzle of Re-exports through Kyrgyz Bazaars - Kaminski, B.; Raballand, G. (2012)
Relying on mirror foreign trade statistics and their reconciliation with official data on balance of payments, two economists demonstrate the important role of bazaars as major conduits of trade in Central Asia, and particularly of Kyrgyz bazaars for the entry of Chinese consumer goods into the region. The authors estimate that in recent years up to three quarters of the goods imported by Kyrgyzstan have been unofficially re-exported to other Central Asian countries, generating substantial income for the Kyrgyz economy. A concluding section explores the implications of the re-export trade for Kyrgyzstan (e.g., positive spillovers for domestic light industry) as well as the potential emergence of new competitors (e.g., Kazakhstan). Journal of Economic Literature, Classification Numbers: F100, F170, F470. 5 tables, 17 references.